Pengaruh Radiasi Neutron Terhadap Waktu Relaksasi Spin-Kisi (T1) Pada Polimer Polivinil Klorida (Pvc) dengan Spektroskopi Nmr Pulsa - Susilawati Susilawati (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
A research measurement of spin-lattice relaxation time (T1) with a pulse NMR spectrometer as well as a test of strength (tensile test and compression test) polymer material PVC (Poly Vinyl Chloride) with tools united-1 test system SFM SFM-30. The study aims to investigate the influence of the neutron fluence on the spin-lattice relaxation time (T1) and to determine the PVC polymer material strength test. On the measurement of the spin-lattice relaxation time (T1) is used method pulse 180o-t-90o and pulse method 90o-t-90o, by means of NMR minispec P.20. Measurement of PVC polymer material strength testing using tools united-1 test system SFM SFM-30. The results showed that the spin-lattice relaxation time (T1) PVC polymer influenced by variations in relaxation times (fluence) neutrons. From the graph of the spin-lattice relaxation time (T1) vs. neutron fluence with the method 90o-t-90o obtained increases and decreases in the value of T1. The value of the spin-lattice relaxation time at the minimum fluence 34.56x1016n/cm2, and the average value of the minimum T1 is (271.1ÃÂ±5.4) for the milli second pulse method 180o-t-90o and the average value The minimum T1 is (263.5ÃÂ±5.3) for the milli second pulse method 90o-t-90o. The value of the spin-lattice relaxation time at the maximum fluence 60.98 x 1016 n/cm2, the average value of the minimum T1 was (481.9ÃÂ±10.1) milli second to the method also 180o-t-90o and the average value of T1 The minimum was (482.5ÃÂ±9.7) for the milli second pulse method 90o-t-90o. Test the strength of the PVC polymer is affected by the neutron fluence. Graph PVC polymer material strength test vs. neutron fluence obtained increases and decreases in the value of the strength of the PVC polymer. Value of the minimum strength of the PVC polymer materials at fluence 34.56 x 1016 n/cm2, the average value of the minimum ÃÆ is (9.5ÃÂ± 0.1) MPa for tensile test, and the average value is the minimum ÃÆ (38.4ÃÂ±0.1) MPa for compression test. Value of the maximum power of the PVC polymer materials at fluence 60.98x1016n/cm2, the average value of the maximum ÃÆ is (43.2ÃÂ±0.9) MPa for tensile test and the average value of the maximum ÃÆ is (55.4ÃÂ±1.1) MPa for compression test.